2007
DOI: 10.1111/j.1526-4610.2007.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of a Major Depressive Episode in Primary Care Patients With a Chief Complaint of Headache

Abstract: Objective.—To identify the indicators of major depressive episode (MDE) in primary care patients with a chief complaint of headache. Background.—MDE is very frequent among headache patients in primary care. However, primary care physicians often fail to recognize the coexistence of MDE. Methods.—A total of 177 consecutive new adult patients who visited 19 primary care clinics from January 2002 to December 2002 with a chief complaint of headache were enrolled in the study. All subjects completed a self‐report q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Moreover, validated screening instruments, such as the Patient Health Questionnaire 55 and the Insomnia Severity Index, 56 can be easily administered to MOH patients by primary care physicians to identify depressive symptoms and insomnia. 27,[57][58][59] Thus, early and comprehensive assessment of these risk factors is necessary for medical and mental health professionals to consider while evaluating and treating patients with MOH to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, validated screening instruments, such as the Patient Health Questionnaire 55 and the Insomnia Severity Index, 56 can be easily administered to MOH patients by primary care physicians to identify depressive symptoms and insomnia. 27,[57][58][59] Thus, early and comprehensive assessment of these risk factors is necessary for medical and mental health professionals to consider while evaluating and treating patients with MOH to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…reported a prevalence of 25.4% major depressive episodes in primary care patients with a chief complaint of headache. [ 10 ] However, other depression subtypes were not assessed. Another case-control study found that 32% of primary care patients with a chief complaint of headache were diagnosed with a major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Maeno et al . [ 10 ] reported that headache duration predicts a higher risk for a major depressive episode. Our study added another perspective regarding the relationship between headache duration and episodes of a psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible reason for higher rates of undiagnosed neurological disorders (migraine headache and epilepsy) might be due to a significant overlap between symptoms of severe psychiatric disorder and neurological disorders. For instance, a study conducted by Moeno et.al found that more than one fourth (25.4%) of patients with major depressive disorders visited a primary care setting with a chief complaint of headache [48]. Similarly, a case-control study conducted by Marlow et.al reported that 32% of patients who reported headaches as the main symptoms were diagnosed with major depressive disorders [49].…”
Section: The Prevalence Of Undiagnosed Neurological Disorders Diseasementioning
confidence: 99%